Effect of accelerated organic fertilizer on coffee seedlings (Coffea arabica L.) - Cosme De La Cruz, Roberto (2020)
The objective of the research was to evaluate the effect of accelerated organic fertilizer on the growth and development of coffee plants (Coffea arabica L.), Catimor variety, in the Greenhouse of the Experimental Center and Multipurpose Laboratory of the Instituto Nacional de Innovación Agraria (INIA), district La Molina, department of Lima, Peru. The completely random design was used, with two treatments: treatment 1 (without accelerated organic fertilizer) and treatment 2 (with accelerated organic fertilizer). The following were evaluated: plant height, number of branches, stem diameter, leaf width and length, percentage of dry matter, nitrogen concentration, phosphorus, potassium and calcium in the leaves. The results showed that the use of accelerated organic fertilizer in coffee plants stimulates the variables plant height (24,76 cm), stem diameter (5,74 mm), nitrogen concentration (2,33%), phosphorus concentration (0,17%), calcium concentration (1,61%), but without statistical difference between treatments. In the number of branches per plant, the treatment with accelerated organic fertilizer had the highest number of branches with 3,25 branches per plant, compared to the treatment without accelerated organic fertilizer with 1,5 branches per plant.